Cognitive emotion regulation types among Malaysian graduates - Panahi, Soheila; Md. Yunus, Aida Suraya; Roslan, Samsilah (Marsland Press, 2013)
This study aims to discern the convergent and discriminate validity of cognitive emotion regulation and to make a comparison of cognitive emotion regulation based on demographic profile of graduate students. A total number of 534 graduate students of age from 19 to 45 years were surveyed in Universiti Putra Malaysia. The convergent and discriminant validity analysis using Stats Tools Package revealed that there are high cognitive emotion regulation strategies among Malaysian graduate students. The descriptive analysis showed that the mean score was highest for positive reappraisal, followed by planning. The ANOVA test showed a significant difference in reappraisal strategy between students from different faculties. Similarly, the ANOVA test showed that there was a significant difference between planning and acceptance strategies among students of different races. The ANOVA further revealed the significant differences in self-blame, other-blame, and rumination strategies among different age groups. The independent t-test also revealed that there were significant differences in self-blame, other-blame, catastrophysing, and putting into perspective between males and females. However, the analysis showed no significant differences in cognitive emotion regulation strategies based on the semester, family size, marital and employment status between graduates.